2018
DOI: 10.2147/cia.s183102
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thiamine deficiency in older hospitalized patients

Abstract: PurposeDespite some reports of high prevalence of thiamine deficiency in elderly people, the reported prevalence is controversial mainly due to the methods used in assessing thiamin concentrations. In this study, we sought to investigate the prevalence of vitamin B1 deficiency, using the high-performance liquid chromatography (HPLC) method, among older hospitalized patients.Patients and methodsThis cross-sectional study retrospectively analyzed the results of routine measurements of vitamin B1 of 238 older pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Serum thiamine concentration was measured using high-performance liquid chromatography at an outside laboratory (SRL, Inc. Tokyo). This method is precise and rapid, and is less susceptible to factors that alter enzyme activity, while providing a more sensitive assay for screening TD in a clinical setting and for research purposes [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Serum thiamine concentration was measured using high-performance liquid chromatography at an outside laboratory (SRL, Inc. Tokyo). This method is precise and rapid, and is less susceptible to factors that alter enzyme activity, while providing a more sensitive assay for screening TD in a clinical setting and for research purposes [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, another study failed to show any thiamine deficiency in a group of elderly patients. However, this might not be indicative as low thiamine metabolism was not investigated, nor was there any evidence of supplement consumption among subjects [ 25 ].…”
Section: B Vitamins Orchestration In Different Life Stagesmentioning
confidence: 99%
“…Likewise, inadequate vitamin intake is prevalent in older adults. Some studies have shown a higher risk of deficiencies in senior citizens living alone or in a psychiatric or nursing home environment [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%